ANALISIS TERHADAP PELAKSANAAN KERAHASIAAN BANK BERDASARKANUU NO. 7 TAHUN 1992 TENTANG PERBANKAN SEBAGAIMANA TELAH DIUBAH DENGAN UU NO. 10 TAHUN 1998 PADA PT. BANK PEMBANGUNAN DAERAH KALIMANTAN BARAT - ANDRI KUSWARA, SE, MM A.212.1071, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT Bank secrecy is everything related to information about customers and their savings. Communities will entrust their funds in the bank or use the services of the bank if the protected information about the identity of the customer such as name, address, and account number at a bank and a store of savings. In this regard, the study is